PERSEPSI ULAMA KOTA BANJARMASIN TERHADAP TINDAKAN ANAK YANG MENEMPATKAN ORANG TUANYA DI PANTI JOMPO DALAM PERSPEKTIF ETIKA ISLAM - Rahmawati, Rahmawati; Syadzali, Ahmad (Jurnal Studia Insania, 2015)
This study wants to tell about a fact that there many people have less awareness with their duty as a child to theirÂ parents aged, moreover when they have a good position and have many activities with his jobs. Some children putÂ their parents in an old folksâ home because they cannot take after them well. This action absolutely does notÂ reflect an implementation of command of Allah that is to dedicate to their parents. Because of that, it needsÂ to have responses of Ulama about this problem and it needs to get explanations about childrenâs ethics on theirÂ parents as well as teaching in Islam.